COMPARATIVE EFFICACY OF PROTON PUMP INHIBITORS VS. H2 RECEPTOR ANTAGONISTS IN THE TREATMENT OF GASTROESOPHAGEAL REFLUX DISEASE - KHAN , S; MUNEEB , A; AHMAD, MS (Biological and Clinical Sciences Research Journal, 2024)
Gastroesophageal reflux disease (GERD) is a common condition characterized by acid reflux into the esophagus, leading to symptoms such as heartburn and regurgitation. Objective: To compare the efficacy of Proton Pump Inhibitors (PPIs) and H2 Receptor Antagonists (H2RAs) in treating GERD in a cohort of 800 patients, assessing symptom relief, healing rates, and side effects. Methods: A total of 800 patients diagnosed with GERD were added to receive either PPIs (n=400) or H2RAs (n=400) for a treatment period of 8 weeks. The primary outcome was improved GERD symptoms, measured using a standardized GERD symptom questionnaire. Results: The study found that the PPI group demonstrated a significantly higher improvement in symptom relief, with 78% achieving complete symptom resolution compared to 54% in the H2RA group (p < 0.05). Esophageal healing rates were also superior in the PPI group, with 84% showing complete healing compared to 62% in the H2RA group. Furthermore, the time to symptom relief was shorter in the PPI group (average of 5 days) compared to the H2RA group (8 days). Adverse effects were minimal and comparable between the two groups, with mild headaches (8% vs. 6%) and gastrointestinal discomfort (10% vs. 9%) being the most frequently reported. Conclusion: Proton Pump Inhibitors are more effective than H2 Receptor Antagonists in relieving symptoms, accelerating symptom resolution, and promoting esophageal healing in patients with GERD. Although both treatments are generally well-tolerated, PPIs remain the preferred choice for patients requiring more potent acid suppression due to their superior efficacy.